Pengaruh Outdoor Learning terhadap Sikap Peduli Lingkungan Anak Usia 5–6 Tahun Kelompok B di PAUD Ar-Rahman, Desa Galang Tinggi, Kecamatan Banyuasin III - Gina Sonia; Fahmi; Kurnia Dewi; Maryamah; Yecha Febrieanitha Putri (Inovasi Pendidikan dan Anak Usia Dini, 2025)
This research is entitled "The effect of outdoor learning on environmental care attitudes in group B children aged 5-6 years at PAUD Ar-Rahman, Galang Tinggi Village, Banyuasin III District, Banyuasin Regency". The problem in this study is the low attitude of caring for the environment. This study aims to find out whether there is an influence of outdoor learning on environmental care attitudes in group B children aged 5-6 years at Ar-Rahman PAUD, Galang Tinggi Village, Banyuasin III District, Banyuasin Regency. This type of research is Pre-Experimental with One Group Pre Test - Post Test design. The sample in this study amounted to 15 children consisting of 7 boys and 8 girls. The data collection technique in this study uses observation, tests and documentation. The data analysis techniques used in this study are normality test, homogeneity test, and hypothesis test. The results of the hypothesis were obtained after the initial test (pre test) and final test (posttest), then the researcher analyzes the results of the research. The results of data analysis in proving the hypothesis test were obtained tcount = 71.132 while to determine the table with a significance level of 5%, a ttable of 2.145 was obtained. So it can be concluded that > ttable calculation, Ha is accepted and Ho is rejected, which means that there is a significant influence of the use of outdoor learning on environmental care attitudes in group B children at PAUD Ar-Rahman, Galang Tinggi Village, Banyuasin III District, Banyuasin Regency.